THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE, INVESTMENT EFFICIENCY AND FIRM PERFORMANCE IN COMPANIES LISTED ON THE SHANGHAI STOCK EXCHANGE OF CHINA - QIANQIAN, TANG (2022)
Corporate governance is closely related to the interests of corporate stakeholders and involves the future development of enterprises. Therefore, most people believe that maintaining a high level of governance is the advantage of enterprises to obtain core competitiveness. However, in real life, there are still endless financial scandals and inefficient investments of listed companies, which not only hit the confidence of investors but also hinder the development of the economy. Previous literature finds that most corporate governance measures improve enterprises' investment efficiency and performance, but there are conflicting conclusions for some specific governance measures. This paper collects primary data and uses the quantitative analysis method to study the impact of corporate governance on investment efficiency and firm performance by taking listed firms in the China from 2010 to 2020 as research objectives. Moreover, it also investigates whether investment efficiency has a mediating effect on corporate governance and firm performance. In this paper, the investment efficiency and performance of the company are measured, and then regression analysis, mediation effect analysis, and robustness test are conducted. The results show that board independence, power balance with shareholders, and executive ownership have positive effects on investment efficiency and corporate performance. In contrast, the separation of two positions has no statistically significant relationship with the dependent variable. In addition, investment efficiency does have a mediating effect. This paper provides a new perspective to study corporate governance from theoretical and practical levels, adds investment efficiency as a mediator variable, and adopts a more objective factor analysis method to measure corporate performance.